2016
DOI: 10.5296/ber.v6i2.9831
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Transformational Leadership and Employee Retention among Healthcare Professionals in the United States

Abstract: With the endemic health care professional shortage seen both in the United States as well as globally, retaining staff is a high priority. Much like other organizations who rely on human capital, health care professionals are the most important resource for improving patient outcomes, and for achieving organizational performance. Leaders must effectively manage their employees in order to retain top talent and meet organizational goals. One reason for high turnover rates among healthcare professionals is the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Against the background of Bass (1985), the TL theory best explains the model constructed for this study. The theory supports the idea that transformational leaders modify the behavior of subordinates (Burns, 1978a), resulting in a higher ER (Sow et al, 2016). Furthermore, TL increases the intellectual ability of employees (Fletcher et al, 2019).…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…Against the background of Bass (1985), the TL theory best explains the model constructed for this study. The theory supports the idea that transformational leaders modify the behavior of subordinates (Burns, 1978a), resulting in a higher ER (Sow et al, 2016). Furthermore, TL increases the intellectual ability of employees (Fletcher et al, 2019).…”
Section: Introductionsupporting
confidence: 76%
“…Studies also found that organizational justice theory impacts the effects on OCB through perceived restorativeness (Bellini et al, 2019). However, studies on TL have examined TL theory and its four dimensions significantly affecting OCB (Jiang et al, 2017) and ER (Adekanbi, 2016;Sow et al, 2016). It is based on the view that transformational leaders transform their followers by changing their insights, ambitions, morals, and potential (Bass, 1985).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
See 3 more Smart Citations